Ca2+ imbalance caused by ERdj5 deletion affects mitochondrial fragmentation - Riyuji Yamashita (Nature Portfolio, 2021)
Abstract The endoplasmic reticulum (ER) is the organelle responsible for the folding of secretory/membrane proteins and acts as a dynamic calcium ion (Ca2+) store involved in various cellular signalling pathways. Previously, we reported that the ER-resident disulfide reductase ERdj5 is involved in the ER-associated degradation (ERAD) of misfolded proteins in the ER and the activation of SERCA2b, a Ca2+ pump on the ER membrane. These results highlighted the importance of the regulation of redox activity in both Ca2+ and protein homeostasis in the ER. Here, we show that the deletion of ERdj5 causes an imbalance in intracellular Ca2+ homeostasis, the activation of Drp1, a cytosolic GTPase involved in mitochondrial fission, and finally the aberrant fragmentation of mitochondria, which affects cell viability as well as phenotype with features of cellular senescence. Thus, ERdj5-mediated regulation of intracellular Ca2+ is essential for the maintenance of mitochondrial homeostasis involved in cellular senescence.